2019
DOI: 10.3390/w11050912
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impact on the Evolution of the Saline Lakes of the Soan-Sakaser Valley (Central Salt Range; Pakistan): Evidences from Hydrochemistry and Water (δD, δ18O) and Chlorine (δ37Cl) Stable Isotopes

Abstract: The surfaces of saline lakes are shrinking at a threatening rate worldwide. Likewise, the Uchhali complex (formed by three saltwater lakes located in the Salt Range, Pakistan) that serves as a major regional source of water for humans and as a habitat for water birds must be monitored. With this objective in mind, we conducted a study coupling hydrochemistry and stable isotope compositions (δ37Cl, δ18O and δD) in order to characterize its hydrochemical properties and the main processes controlling them. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Burning fossil fuels, which is the major cause of global climate change, is related to the decrease of the water level of many lakes and, consequently, increased desiccated periods (both frequency and duration) and related impacts as increased penetration of ultraviolet radiation. A few lakes in Pakistan are examples of this case, with reduced habitat representativeness and biodiversity and altered life cycles of aquatic species [23]. Many other ISL have been referred to with decreasing water levels related to climate change [18,[24][25][26].…”
Section: The Conservation Of Inland Salt Lakes and Their Status In 2025mentioning
confidence: 99%
“…Burning fossil fuels, which is the major cause of global climate change, is related to the decrease of the water level of many lakes and, consequently, increased desiccated periods (both frequency and duration) and related impacts as increased penetration of ultraviolet radiation. A few lakes in Pakistan are examples of this case, with reduced habitat representativeness and biodiversity and altered life cycles of aquatic species [23]. Many other ISL have been referred to with decreasing water levels related to climate change [18,[24][25][26].…”
Section: The Conservation Of Inland Salt Lakes and Their Status In 2025mentioning
confidence: 99%
“…The study of the Cl/Br ratio has proved to be one of the most effective and sensitive indexes when defining the geological environment, brine concentrations and the depositional stages associated to the brine evaporation process (e.g. Han et al, 2019;Hussain et al, 2019). Experiments have demonstrated that this Cl/Br ratio is related to the brine and salt evolution (Braitsch, 1962): the more advanced brine solutions produce lower Cl/Br ratios in the precipitates (Eggenkamp et al, 2019a;Eggenkamp et al, 2019b).…”
Section: Halite Geochemistrymentioning
confidence: 99%
“…The major rock salts deposits in Pakistan are located in the Salt Range area and in the Kohat basin (KB) (e.g. Hussain et al, 2019;Hussain et al, 2020a;Hussain et al, 2020b;Hussain et al, 2021). The Precambrian Salt Range is considered as the main and oldest salt deposits in the sub-continent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area displays wide varieties of structural styles, salt tectonics, and deposition in varied depositional settings. The Salt Range Formation is one of the excellent laboratory experiments to display the evaporative system in Pakistan, but unfortunately it is the least studied formation, particularly with reference to isotopic studies [26,27].…”
Section: Introductionmentioning
confidence: 99%